Some lessons from the financial crisis for the economic analysis - Geoff Kenny; Julian Morgan (European Central Bank (ECB), 2011)
The economics profession in general, and economic forecasters in particular, have faced some understandable criticism for their failure to predict the timing and severity of the recent economic crisis. In this paper, we offer some assessment of the performance of the Economic Analysis conducted at the ECB both in the run up to and since the onset of the crisis. Drawing on this assessment, we then offer some indications of how the analysis of economic developments could be improved looking forward. The key priorities identifi ed include the need to: i) extend existing tools and/or develop new tools to account for important feedback mechanisms, for instance, improved real-fi nancial linkages and non-linear dynamics; ii) develop ways to handle the complexity arising from the presence of multiple models and alternative economic paradigms; and iii) given the limitations of point forecasts, to further develop risk and scenario analysis around baseline projections.
Keywords: C43; D91; E31; E52; E58; 330; euro area; financial crisis; MACRO ECONOMIC FORECASTING